HUBUNGAN ANTARA KARAKTERISTIK HIS DENGAN LAMA PERSALINAN DI PMB NGUDI SARAS NGRINGO, JATEN, KARANGANYAR - N. Kadek Sri Eka Putri; Yeni Anggraini; Suwarnisih Suwarnisih (Jurnal Ilmu Keperawatan dan Kebidanan, 2023)
Labor and birth are physiological things that will be experienced by almost all women. However, maternal mortality and morbidity is a major problem in developing countries. About 76% of maternal deaths occur in the labor phase. There are several factors that cause maternal death, one of which is prolonged labor, where on average prolonged labor causes maternal mortality by 8% in the world and in Indonesia by 9%. Prolonged labor can be bad for both the mother and the baby. The purpose of this study was to determine the relationship between His characteristics and length of delivery at PMB Ngudi Saras Ngringo, Jaten Karanganyar. The research method used in this research is analytic observational. The population of this study were all mothers who gave birth at PMB Ngudi Saras Ngringo, Jaten, Karanganyar from January to December 2021. With a total sample of 72 respondents. Data analysis using chi squared (X2). The results of the study obtained the value of chi squared count (61,411) chi squared table (5,991) with a probability of 0.000 0.05, so it can be concluded that there is a relationship between his characteristics and the length of labor. The contingency coefficient obtained a value of 0.678 so that it can be concluded that the level of closeness of the relationship between his characteristics and the length of labor is included in the strong category.